Crybaby lois - Pascal, Francine (Bantam Books New York, 1990)
Elizabeth Wakefield comes to the aid of Lois Waller, a young girl who is afraid of everything and everybody, teaching Lois how to ride a bicycle, stand up for herself, and cope with the other kids' teasing